2019
DOI: 10.1136/bmjoq-2018-000560
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate utilisation of cardiac telemetry monitoring: a quality improvement project

Abstract: For hospitals located in the United States, appropriate use of cardiac telemetry monitoring can be achieved resulting in cost savings to healthcare systems. Our institution has a limited number of telemetry beds, increasing the need for appropriate use of telemetry monitoring to minimise delays in patient care, reduce alarm fatigue, and decrease interruptions in patient care.This quality improvement project was conducted in a single academic medical centre in Kansas City, Kansas. The aim of the project was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…A particularity of the present case was the use of cardiac telemetry (26). Continuous monitoring with cardiac telemetry assisted the cardiologists in understanding if their intervention was required, thus reducing the risk for healthcare workers, whilst not delaying any intervention.…”
Section: Discussionmentioning
confidence: 98%
“…A particularity of the present case was the use of cardiac telemetry (26). Continuous monitoring with cardiac telemetry assisted the cardiologists in understanding if their intervention was required, thus reducing the risk for healthcare workers, whilst not delaying any intervention.…”
Section: Discussionmentioning
confidence: 98%
“…Reminding clinicians to reassess a patient’s need for telemetry, daily bloodwork, or urinary catheter builds on education. Indicators or pop-ups in the electronic medical record (EMR), clinical decision supports, and questioning the need for ongoing telemetry in daily rounds have reduced duration of telemetry monitoring and number of orders placed . Clinical decision alerts that display previous stable laboratory results decrease bloodwork utilization .…”
Section: Embed Remindersmentioning
confidence: 99%
“…6,7,15,16 Our intervention was chosen based on the literature which showed that EMRbased systems could alter telemetry ordering and was modified for our local context. 6,7,16 Stoltzfus et al also showed that EMR-based interventions were more successful than nursing huddles or education-based interventions. While education models and feedback showed benefit, they lacked efficacy over time.…”
Section: Baseline Auditmentioning
confidence: 99%